2020
DOI: 10.3390/molecules25081807
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds Rosmarinic Acid and Carvacrol Counteract Aluminium-Induced Oxidative Stress

Abstract: Aluminum accumulation, glutathione (GSH) and malondialdehyde (MDA) concentrations as well as catalase (CAT) and superoxide dismutase (SOD) activities were determined in erythrocytes and brain and liver homogenates of BALB/c mice treated with Al 3+ (7.5 mg/kg/day (0.15 LD 50 ) as AlCl 3 (37.08 mg/kg/day), whereas HCl (30.41 mg/kg/day) was used as Cl − control, the treatments were performed for 21 days, i.p., in the presence and absence of rosmarinic acid (0.2805 mg/kg/day (0.05 LD 50 ), 21 days, i.g.) or carvac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 66 publications
6
22
0
Order By: Relevance
“…E) in diabetic rats [101]. This result was confirmed by Baranauskaite et al [97] and Thingore et al [106], which proved a decrease in MDA concentration and an increase in SOD and CAT activities after treatment with rosmarinic acid. On the other hand, the study of Dianat and their colleagues demonstrated that vanillic acid reduced the malondialdehyde content, as well as elevated SOD, CAT, and GPx activities on ischemia-reperfusion-induced oxidative stress in isolated rat hearts [99].…”
Section: Vanillic Acidsupporting
confidence: 59%
See 1 more Smart Citation
“…E) in diabetic rats [101]. This result was confirmed by Baranauskaite et al [97] and Thingore et al [106], which proved a decrease in MDA concentration and an increase in SOD and CAT activities after treatment with rosmarinic acid. On the other hand, the study of Dianat and their colleagues demonstrated that vanillic acid reduced the malondialdehyde content, as well as elevated SOD, CAT, and GPx activities on ischemia-reperfusion-induced oxidative stress in isolated rat hearts [99].…”
Section: Vanillic Acidsupporting
confidence: 59%
“…Numerous reports have evaluated the antioxidant activities of phenolic acids (Table 2) [97][98][99][100][101][102][103][104][105][106][107][108]. In a study reported by Tolba et al [107], caffeic acid showed a potential antioxidant activity by enhancing glutathione peroxidase content and SOD activity and significantly decreasing femur bone MDA in glucocorticoid-induced osteoporosis in vivo.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…Elevated MDA levels and decreased CAT activity in AlCl 3 -treated rats were also found in a study by Bouasla et al [ 37 ], suggesting that these changes may be related to peroxidative damage to biological membranes caused by increased reactive Fe 2+ levels and the inactivation of enzymes involved in antioxidant defense [ 37 ]. Our previous study proved the antioxidant activity of the Cannabis sativa L. extract in vitro, which was related to the total amount of polyphenols [ 21 ] due to their ability to chelate metal ions and scavenge reactive oxygen species [ 27 ]. The present study showed the ability of this extract to stimulate the antioxidant defense system in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of brain and liver homogenates was evaluated according to the procedure described by Baranauskaite et al [ 21 ]. Following cervical dislocation, the animal brain and liver were removed, washed, and immediately cooled on ice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation